2023
DOI: 10.3390/biomedicines11082106
|View full text |Cite
|
Sign up to set email alerts
|

The Value of White Cell Inflammatory Biomarkers as Potential Predictors for Diabetic Retinopathy in Type 2 Diabetes Mellitus (T2DM)

Abstract: The pathogenesis of diabetic retinopathy is still challenging, with recent evidence proving the key role of inflammation in the damage of the retinal neurovascular unit. This study aims to investigate the predictive value of the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte (PLR), lymphocyte-to-monocyte ratio (LMR), and systemic inflammation index (SII) for diabetic retinopathy (DR) and its severity. We performed a retrospective study on 129 T2DM patients, divided into three groups: without reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The NLR, MLR, PLR, and SII did not show significant differences in moderate and severe NPDR in our study, which is in line with other studies [23][24][25]. Zeng et al showed that the NLR, PLR, and MLR were significantly higher in patients with DR compared to patients without DR; however, there was no relationship between the MLR, NLR, or PLR and severity of retinopathy [23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The NLR, MLR, PLR, and SII did not show significant differences in moderate and severe NPDR in our study, which is in line with other studies [23][24][25]. Zeng et al showed that the NLR, PLR, and MLR were significantly higher in patients with DR compared to patients without DR; however, there was no relationship between the MLR, NLR, or PLR and severity of retinopathy [23].…”
Section: Discussionsupporting
confidence: 90%
“…Zeng et al showed that the NLR, PLR, and MLR were significantly higher in patients with DR compared to patients without DR; however, there was no relationship between the MLR, NLR, or PLR and severity of retinopathy [23]. According to Dascalu et al, the NLR, MLR, and SII were significantly higher in patients with proliferative diabetic retinopathy compared to those with NPDR or without DR [24]. The aforementioned biomarkers are more related to DME, which was also recently validated in the research by Yanxia et al, who found notable variations in biomarkers in various types of DME [25].…”
Section: Discussionmentioning
confidence: 99%
“…If optimally implemented, these effects could further increase the potential of exercise to slow down the progression of T2DM and its complications (e.g., diabetic retinopathy or neuropathy) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various morphological abnormalities in the retinal vasculature, such as increased artery tortuosity, altered arteriovenous width and ratio (AVR), arteriovenous (AV) nicking, and the onset of macular edema in severe cases, characterize hypertensive retinopathy (HR) [1] and diabetic retinopathy [2]. These abnormalities can lead to reduced visual acuity and an increased risk of stroke later in life, suggesting inflammation in the retinal vasculature.…”
Section: Introductionmentioning
confidence: 99%